1998
DOI: 10.1111/j.1600-0897.1998.tb00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental Transport of Maternal Immunoglobulin G

Abstract: The fetal IgG concentrations exceed maternal IgG concentrations after the 35th week of pregnancy. The fetal IgG concentrations are extremely low in the beginning of pregnancy, they exceed 2.5 g/L at > 25 pregnancy weeks, and they reach 5 g/L at pregnancy week 30.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 11 publications
5
42
0
1
Order By: Relevance
“…HERZ et al [9] proposed several mechanisms of prenatal regulation of foetal immunity including: transfer of antibodies, transfer of immune complexes, and transfer of cytokines or other soluble molecules via the placental membrane. Although allergenspecific maternal IgG might be a candidate for a foetal-maternal interface [20,21], transplacental transfer of allergen-specific IgG was not considered to be a major mechanism for maternal regulation of allergen-specific immunity in infancy [7]. WARNER et al [8] reported that the concentration of IL-10 in the amniotic fluid differed according to the atopy status of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…HERZ et al [9] proposed several mechanisms of prenatal regulation of foetal immunity including: transfer of antibodies, transfer of immune complexes, and transfer of cytokines or other soluble molecules via the placental membrane. Although allergenspecific maternal IgG might be a candidate for a foetal-maternal interface [20,21], transplacental transfer of allergen-specific IgG was not considered to be a major mechanism for maternal regulation of allergen-specific immunity in infancy [7]. WARNER et al [8] reported that the concentration of IL-10 in the amniotic fluid differed according to the atopy status of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Since antibody transfer occurs mainly during the third trimester of pregnancy, preterm infants have low levels of maternal antibodies (5,21,26,28,31,41,46). Placental transfer has also been found to be less efficient in infants in developing countries than in industrialized countries (22).…”
Section: Discussionmentioning
confidence: 99%
“…Newborns are protected against measles by maternal antibodies actively transferred via the placenta during the last trimester of pregnancy (41,46). These maternal antibodies disappear during the first months of life as the newborn's own immune system develops.…”
Section: Discussionmentioning
confidence: 99%
“…The electron spin resonance spectra of the isatin anion radical was also recorded and revealed that the monoanion radical exists in equilibrium with the dianion radical in the solvents employed 560 . DSC thermograms of some alkylisatins were also recorded 558 .…”
Section: Further Spectroscopic Datamentioning
confidence: 99%
“…This property has been exploited for the determination of the level of this aminoacid in pollens [560][561][562][563] and other vegetal materials 564 Scheme 136. The Chemistry of Isatins Vol.…”
Section: Organic Analytical Chemistrymentioning
confidence: 99%